Transcriptomic resources for an endemic Neotropical plant lineage (Gesneriaceae)1. (12th April 2017) - Serrano‐Serrano, Martha L.; Marcionetti, Anna; Perret, Mathieu; Salamin, Nicolas
Abstract : Premise of the study: Despite the extensive phenotypic variation that characterizes the Gesneriaceae family, there is a lack of genomic resources to investigate the molecular basis of their diversity. We developed and compared the transcriptomes for two species of the Neotropical lineage of the Gesneriaceae. Methods and Results: Illumina sequencing and de novo assembly of floral and leaf samples were used to generate multigene sequence data for Sinningia eumorpha and S. magnifica, two species endemic to the Brazilian Atlantic Forest. A total of 300 million reads were used to assemble the transcriptomes, with an average of 92, 038 transcripts and 43, 506 genes per species. The transcriptomes showed good quality metrics, with the presence of all eukaryotic core genes, and an equal representation of clusters of orthologous groups (COG) classifications between species. The orthologous search produced 8602 groups, with 15–20% of them annotated using BLAST tools. Discussion: This study provides the first step toward a comprehensive multispecies transcriptome characterization of the Gesneriaceae family. These resources are the basis for comparative analyses in this species‐rich Neotropical plant group; they will also allow the investigation of the evolutionary importance of multiple metabolic pathways and phenotypic diversity, as well as developmental programs in these nonmodel species.